POTENTIAL ANTIOXIDANT EFFICACY OF THE SECONDARY METABOLITES ISOLATED FROM CALOCYBE INDICA (VAR.APK2): AN EDIBLE MACROFUNGI - AKBAR BATCHA, PARVEEN NISHA; KUMUTHAKALAVALLI, R. (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Mushrooms have been valued as traditional sources of natural bioactive compounds for many centuries and targeted as promising therapeutic agents. The bioactive mycomolecules of mushrooms are reported to have antioxidant, antitumor, antidiabetic, anti-inflammatory, and antimicrobial activity, which are the important medicinal targets in terms of drug discovery today. Hence, an attempt was made in the present study, to evaluate the immunomodulatory and oxidative process of secondary metabolites from the milky mushroom Calocybe indica (P&C) var.APK2 using radical scavenging assays. Methods: The fruiting bodies of milky mushrooms were found to produce an array of mycomolecules such as phenols, flavonoids, alkaloids, tannins, terpenoids, steroids, and saponins in their methanolic extract which was confirmed using Fourier-transform infrared spectrophotometer (FT-IR) analysis and standard phytochemical studies; hence, chromatography fractions of these mushroom seem greatly promising biological activities including antioxidants. Results: The functional analysis of the secondary metabolites of these macrofungi was evaluated by the separation of potential fractions using preparative thin-layer chromatography (TLC) that revealed seven distinct bands with Rf values of 0.14, 0.26, 0.31, 0.42, 0.52, 0.70, and 0.82; the antioxidant activity was determined through TLC in situ bio autography. The quenching property of metabolite compound which was ranging from 19% to 77.9% and the half effective concentration values of 2,2-diphenyl-1-picrylhydrazyl and hydroxyl radical scavenging activity was recorded as 64.26 μg/ml and 54.5 μg/ml sample concentration, respectively. The active mycomolecules of C. indica from the TLC was, further, confirmed using Gas Chromatography–Mass Spectrometry studies. Conclusion: The present investigation of the study revealed that the antioxidant efficacy of edible milky mushroom may be further proceeded for in vivo studies for novel drug discovery.